(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article considers the increasing demand for polymer products, particularly the recycling of secondary polymer waste to produce plasticized products. Taking this into account, an innovative technology for manufacturing products based on local secondary polymer waste has been developed and recommended for practical application.